A transient wave of Bhlhe41+ resident macrophages enables remodeling of the developing infarcted myocardium - Yue Xu; Kai Jiang; Fanghua Su; Ruhua Deng; Zhiyang Cheng; Dandan Wang; Yong Yu; Yaozu Xiang (Cell Reports, 2023)
Summary: The immune system plays a critical role during myocardial injury, contributing to repair and remodeling post myocardial infarction (MI). The myocardial infarct and border zone exhibit high heterogeneity, in turn leading to reconstructing macrophage subsets and specific functions. Here we use a combination of single-cell RNA sequencing, spatial transcriptomes, and reporter mice to characterize temporal-spatial dynamics of cardiac macrophage subtype in response to MI. We identify that transient appearance of monocyte-derived Bhlhe41+ Mφs in the “developing” infarct zone peaked at day 7, while other monocyte-derived macrophages are identified in “old” infarct zone. Functional characterization by co-culture of Bhlhe41+ Mφs with cardiomyocytes and fibroblasts or depletion of Bhlhe41+ Mφs unveils a crucial contribution of Bhlhe41+ Mφs in suppression of myofibroblast activation. This work highlights the importance of Bhlhe41+ Mφ phenotype and plasticity in preventing excessive fibrosis and limiting the expansion of developing infarct area.